2007
DOI: 10.5650/jos.56.253
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Auraptene Reduces Helicobacter pylori Colonization of Glandular Stomach Lesions in Mongolian Gerbils

Abstract: We examined the efficacy of auraptene (AUR), an antioxidant agent of a citrus coumarin derivative, for suppressing gastric inflammation introduced by Helicobacter pylori (Hp) infection in Mongolian gerbils (MGs). Hp-infected MGs were placed on diets containing 100 or 500 ppm AUR for 7 weeks. Real-time PCR was used to estimate the Hp population in glandular stomach lesions, and a histological assessment of inflammation was performed. At a dose of 500 ppm, AUR reduced the Hp population to 21.9+/-12.0% of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…This is the first report indicating that lacinartin possesses anti-bacterial properties. Previous studies have shown that auraptene has antibacterial properties against Helicobacter pylori [24,25] . The exact mechanism by which lacinartin and auraptene inhibit bacterial growth is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report indicating that lacinartin possesses anti-bacterial properties. Previous studies have shown that auraptene has antibacterial properties against Helicobacter pylori [24,25] . The exact mechanism by which lacinartin and auraptene inhibit bacterial growth is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…3c). 12) Auraptene (1) is a major coumarin in Citrus plants, and numerous studies have demonstrated 1 to have various biological functions in the peripheral tissues, including anti-inflammatory activity, 13,14) anti-carcinogenic activity, 15,16) anti-Helicobacter activity, 17) and regulatory activity toward hepatic lipid metabolism. 18,19) It has also recently been reported that 1 had the ability to promote neurite outgrowth from PC12 cells.…”
mentioning
confidence: 99%
“…21) Takeda et al have recently shown that auraptene exhibited anti-H. pylori colonization activity in Mongolian gerbils. 22) In this present study, auraptene inhibited H. pylori adhesion to NCI-N87 cells by only 27% (Fig. 2A).…”
Section: Discussionmentioning
confidence: 39%
“…21) Interestingly, Takeda et al have indicated that an oral administration of auraptene inhibited H. pylori colonization in Mongolian gerbils. 22) However, this study did not clarify its mechanisms of action. We thus attempted in this present study to elucidate the molecular mechanism by which auraptene suppresses CD74 in NCI-N87 human gastric carcinoma cells.…”
mentioning
confidence: 96%